Analyzing TCSC and SVC effects in wind power curtailment mitigation. (10th May 2016) - Rasoulzadeh‐akhijahani, Ali; Mosallanejad, Ali
Summary: In recent years, wind energy has a remarkable growth, and the power systems tend to increase the integration of wind power source. However, the existing power systems are not compatible with the effects resulted by the highly integrated wind power sources. Because of the transmission congestion, available produced wind power is not able to be fed into the grid. This paper presents the application of flexible AC transmission system (FACTS) devices for mitigating the wind power curtailment. A framework of multi period optimal power flow problem (MPOPF) is derived for a wind integrated power system. FACTS devices are utilized in such a way that the total wind curtailment during a specific time horizon is reduced. The proposed MPOPF is tested on modified IEEE 30‐bus load flow test system. It is shown that the amount of curtailed wind power is significantly reduced when FACTS devices are optimally allocated. Copyright © 2016 John Wiley & Sons, Ltd.